Preparation of asymmetric membranes and their applications in the restoration of groundwater contaminated by trichloroethylene via two‐step bioremediation technology. Issue 23 (7th July 2014) - Song, Zhenyu; Yang, Wei; Zhang, Jinghui; Bi, Tao; Li, Ye; Yuan, Shanshan
ABSTRACT Asymmetric hollow‐fiber membranes were fabricated via a thermally induced phase‐separation process, and the properties of the membrane were investigated. A bubbleless‐aeration membrane module (BAMM) was designed for the purpose of releasing hydrogen or oxygen. Then, the anaerobic reductive dechlorination (ARD) remediation zone and the aerobic oxidative decomposition (AOD) remediation zone were founded based on the BAMM. The effects of the aeration pressure of hydrogen and oxygen on the oxidation reduction potential (ORP) of the liquid phase were investigated. The groundwater contaminated by trichloroethylene (TCE) was used as the restoring object. The effect of the hydrogen aeration on the ARD process and the effect of the oxygen aeration on the AOD process were also investigated. The results show that the ORP–retention time curve in the ARD zone presented an upward opening parabola of growth, whereas the ORP–retention time curve in the AOD zone presented a downward opening parabola of growth. It took 8 days for TCE to decrease from 500 to 52 μg/L in the ARD zone, whereas it took 24 h for cis‐dichloroethylene to decrease from 52 to 35 μg/L in the AOD zone. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 41176.